Reliability of public private partnership projects under assumptions of cash flow volatility - Henning Schöbener; Christoph Schetter; Andreas Pfnür (Technische Universität Darmstadt, Forschungscenter Betriebliche Immobilienwirtschaft, 2007)
This paper focuses on dynamic financial modelling of recurring cash flow items in PPP projects in operating stage and on risks associated with the volatility of these cash flows. As we concentrate on so-called government-pays schemes, only cash-outflows are considered, such as operating costs, repairs and maintenance expenses, and administration costs, whereas the revenue side is considered to be not at risk. We show different approaches to modelling the uncertainty of recurring operating expenses and explain how to interpret the results. Our analysis is based on the mathematical framework of stochastic processes, which, in finance, are particularly used to describe price series evolutions in capital markets. We apply them to generate variable trajectories of operating costs and integrate them into a stochastic simulation of the financial model.
Keywords: 650; public private partnerships; operating costs; risk modelling; stochastic processes; stochastic simulation; Public-Private Partnership; Cash Flow; Betriebsausgaben; Kostenrechnung; Risikomanagement; Simulation; Stochastischer Prozess